The Value of MR-DWI and T1 Mapping in Indicating Radiation-Induced Soft Tissue Injury - Wang, Zeng; Xiong, Bowen; Kang, Nannan; Pan, Xiaoxian; Wang, Caihong; Su, Li; Xing, Zhen; Hong, Jinsheng (Frontiers in Oncology, 2021)
Objective To explore the value of MR-DWI and T1 mapping in predicting radiation-induced soft tissue fibrosis and its correlation with radiation inflammation. Methods ① a total of 30 C57BL/6 mice were randomly divided into a control group (Nor group), irradiation group (IR group) and irradiation plus glycyrrhetinic acid group (GA group). The IR group and GA group were treated with 6MV X-rays to irradiate the right hind limbs of mice for 30 Gy in a single shot. MRI examinations were performed before and on the 7th day after irradiation to measure the apparent diffusion coefficient (ADC) value and the longitudinal relaxation time (T1) value of the hind limb muscles of the mice. On the 90th day after irradiation, the hind limb contracture was measured, and the right hind limb muscle was taken for HE staining, masson staining, immunohistochemical staining and Western blot analysis to detect the expression of a-SMA and Fibronectin. ② The other 30 mice were grouped randomly as above. On the 7th day after irradiation, the right hind limbs of the mice were examined by MRI to measure the ADC value and T1 value of the thigh muscles, and then the right hind thigh muscles were immediately sacrificed to detect IL-1β, IL-6, TNF-a and TGF-β1 expression with ELISA. Results On the 7th day after irradiation, the ADC values ​​of right hind thigh muscles of mice in Nor group, IR group and GA group were (1.35 ± 0.11)*10-3mm2/s, (1.48 ± 0.07) *10-3mm2/s and (1.36 ± 0.13)*10-3mm2/s, respectively, by which the differences between the IR group and Nor group (P=0.008) and that between IR group and GA group (P=0.013) were statistically significant; T1 values ​​were (1369.7 ± 62.7)ms, (1483.7 ± 127.7)ms and (1304.1 ± 82.3)ms, respectively, with which the differences in the T1 value between the IR group and Nor group (P=0.012) and between IR group and GA group (P<0.001) were also statistically significant. On the 90th day after irradiation, the contracture lengths of the right hind limbs of the three groups of mice were (0.00 ± 0.07)cm, (2.08 ± 0.32)cm, and (1.49 ± 0.70) cm, respectively. There were statistically significant differences in the IR group compared with the Nor group (P<0.001) and the GA group (P=0.030). The ADC value (r=0.379, P=0.039) and T1 value (r=0.377, P=0.040) of the mice’s hindlimbs on Day 7 after irradiation were correlated with the degree of contracture on Day 90 after irradiation; the ADC value (r=0.496, P=0.036) and T1 value (r=0.52, P=0.027) were positively correlated with the Masson staining results and with the expression of α-SMA and Fibronectin. While the ADC value was positively correlated with IL-6 (r=0.553, P=0.002), there was no obvious correlation with IL-1β, TNF-a and TGF-β1; the T1 value was positively correlated with IL-1β (r=0.419, P=0.021), IL-6 (r=0.535, P=0.002) and TNF-a (r=0.540, P=0.002) but not significantly related to TGF-β1 (r=0.155, P=0.413). Conclusion The MR-DWI and T1 mapping values on the 7th day after irradiation can reflect the early condition of tissue inflammation after the soft tissue is irradiated, and the values have a certain correlation with the degree of radiofibrosis of the soft tissue in the later period and may be used as an index to predict radiofibrosis.